2023
DOI: 10.3390/ani13071255
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Causes in Captive Cantabrian capercaillie (Tetrao urogallus cantabricus) in Spain

Abstract: The Cantabrian capercaillie (Tetrao urogallus cantabricus) is one of the most severely threatened subspecies of capercaillie. Its current population range is restricted to a small area of the Cantabrian Mountains (northwestern Spain), with only around 200 individuals remaining. As part of the national strategy for the conservation of the subspecies, the Cantabrian capercaillie Captive Breeding Center of Sobrescobio opened in 2009. Here, we use the information provided by the necropsies performed in this facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The negative results for APEC, Salmonella spp. and C. jejuni were not completely unexpected, once these pathogens have been previously described in other wild free-ranging galliforms, although generally at low prevalences 11 , 50 – 52 , and not necessarily considered part of their normal microbiota 51 . In capercaillies, the presence of E. coli was confirmed in captive and free-ranging birds of Germany, with higher occurrence in the captive individuals 50 .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The negative results for APEC, Salmonella spp. and C. jejuni were not completely unexpected, once these pathogens have been previously described in other wild free-ranging galliforms, although generally at low prevalences 11 , 50 – 52 , and not necessarily considered part of their normal microbiota 51 . In capercaillies, the presence of E. coli was confirmed in captive and free-ranging birds of Germany, with higher occurrence in the captive individuals 50 .…”
Section: Discussionmentioning
confidence: 65%
“…This could also be the case for Pyrenean capercaillies. Recently, García-Rodríguez et al 11 reported several cases of colibacillosis (caused by E. coli ) in captive Cantabrian Capercaillies (i.e., isolated E. coli infections in nine chicks and one adult, and a co-infection by E. coli , Clostridium perfringens , and Enterococcus gallinarum in one chick). The potential impact of this bacterium in free-ranging Pyrenean capercaillie chicks is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, passive autonomous acoustic monitoring has begun to be employed to study this bird's behaviour, status and population dynamics, as well as to improve its conservation management (Abrahams & Denny 2018, Abrahams 2019. Western Capercaillie populations in Central and Western Europe have declined during the twentieth century and the viability of its populations is threatened in many areas due to threats such as habitat destruction and predation (Jahren et al 2016, Gil et al 2020, García-Rodríguez et al 2023. It is globally ranked as of Least Concern (BirdLife International 2016, BirdLife International 2024) but as Endangered in Catalonia (Decret 172/2022).…”
mentioning
confidence: 99%